Behavioural components of information transparency from the perspective of the Quran and its organizational implications - Asghari Hafizullah; Gaeini Abulfazl; Mehrabi Hamzah Amir (Kom: Časopis za Religijske Nauke)
Organizations emerge to fulfil specific objectives, giving rise to expectations from stakeholders and beneficiaries of organization. As we enter the third millennium and people's awareness of their citizenship rights increases, we witness a growth in their expectations of organizations. The rise in stakeholder expectations, coupled with managerial and employee inclinations towards opacity, has led to a lack of transparency and the consequent dissatisfaction of stakeholders. Sustaining organizational transparency requires decision-making and implementation to be transparent, thus fostering stakeholder trust. This necessitates, in Islamic societies, the extraction of transparency components from the Quran as a guide for action, followed by their implementation. This research examines the Behavioural components of information transparency from the perspective of the Quran and its organizational implications. Data collection was conducted through library research, with the method of inquiry utilized for problem formulation and referencing the Quran, and hermeneutics employed for organizational implications of transparency. Findings suggest that consultation, condemnation of trickery, advice and benevolence of the people and the ruler, open communication, prohibition of hiding the truth and the prohibition of secret conversation are among the behavioural components of transparency of information from the perspective of the Quran. Therefore, if there is consultation in organizational decisions, the performance of duties is without pretence, employees and managers are benevolent towards people and each other, decisions and actions are expressed openly in organization, facts are not hidden and there is no slander in organization, which will, consequently, be characterized by transparency.